Edukasi Resiko Jatuh pada Lansia di Puskesmas Cendrawasih Makassar - Agung Sahari; Rahmania Ambarika (Yayasan Habiburrahman Jamalu Bina Ummat, 2026)
The increasing number of elderly people in Indonesia has resulted in an increase in various health problems, one of which is the risk of falls, which can lead to injury, disability, decreased quality of life, and even death. The risk of falls in the elderly is influenced by various factors, such as decreased balance, muscle weakness, impaired vision, chronic diseases, the use of certain medications, and unsafe environmental conditions. The elderly's lack of knowledge regarding risk factors and prevention efforts means that falls are still common in the community. This community service activity aims to increase the knowledge and awareness of the elderly regarding fall risk prevention through health education at the Cendrawasih Community Health Center in Makassar. The activity was implemented through health education using interactive lectures, discussions, question and answer sessions, and the delivery of material using educational media that is easy for participants to understand. The material provided includes fall risk factors, danger signs, home environmental modifications, simple balance exercises, and the importance of physical activity and regular health checks. This educational program is expected to increase the elderly's understanding of fall prevention measures, thereby encouraging behavioral changes towards a healthier, more independent, safe, and productive life. In addition, this activity strengthens the role of community health centers as primary health care facilities in implementing promotive and preventive efforts for the elderly group.